Evaluation of Clinical Outcomes in COVID-19 Patients Receiving Remdesivir in Outpatient Setting: Outcomes in COVID-19 patients receiving outpatient Remdesivir - Goudarzi, Forough; Behnoush, Behnam; Hesari, Elahe; Nateghi, Saeed; Akrami, Majid; Alizadeh, Nafiseh sadat; Arefi, Mohammad; Vaseie, Mohammad; Khosravani, Arezoo; Sani, Roya; Alizadeh, Mahbobeh (Iranian Journal of Pharmaceutical Sciences, 2024)
Remdesivir (RDV) is one of the drugs that showed beneficial effects in treating Coronavirus disease in 2019 (COVID-19). We performed the present study to evaluate the safety of Remdesivir administration in the outpatient setting. In this study, 512 patients with COVID-19 participated. When selected patients came to the hospital for the drug injection on the appointed day, the vital signs and the percentage of oxygen saturation were measured before Remdesivir administration. During and after the injection, if any drug side effects occurred, it was recorded. Laboratory tests, including Complete blood count differential, C-reactive protein, Liver function tests, Blood urea nitrogen, and creatinine, were checked before and between the treatment courses. The mean age of participants was 46.19±14.20 years, and 46.9% were men. 97.4 percent of patients did not experience any side effects following Remdesivir administration. The amounts of laboratory components like White blood cells, Platelet, Alanine aminotransferase, and Blood urea nitrogen were significantly increased. In contrast, Hemoglobin, C-reactive protein, Aspartate aminotransferase, Alkaline phosphatase, and Creatinine levels were significantly decreased following the administration of Remdesivir compared to baseline values.